ESTIMATION OF PHENOLIC CONTENT, FLAVONOID CONTENT, ANTIOXIDANT, AND ALPHA-AMYLASE INHIBITORY ACTIVITY OF SOME SELECTED PLANTS FROM SIRAHA DISTRICT NEPAL - Numer Alam; Sharma, Khaga raj (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The purpose of this research was to estimate the phenolic content, flavonoid content, antioxidant, antibacterial, and α-amylase inhibitory activity of some selected plants such as Anethum sowa, Trigonella foenum-graecum, Lepidium sativum, Cuscuta reflexa, Eclipta alba, Leucas cephalotes, and Tinospora cordifolia collected from Siraha district of Nepal using in vitro studies. Methods: Methanol extracts of these medicinal plants were prepared by cold percolation method. Preliminary phytochemical screening was performed by color differentiation method. Total phenolic and flavonoid content were estimated by Folin-Ciocalteu reagent method and aluminum chloride colorimetric method. Antioxidant potential was evaluated by 2,2-diphenyl-1-picrylhydrazyl radical scavenging assay. Furthermore, the α-amylase enzyme inhibitory activity was studied using starch as a substrate, pancreatic α-amylase as the enzyme, and acarbose as standard. Results: Phytochemical screening showed that the plant extracts were found a rich source of secondary metabolites. The phenolic content estimation showed T. foenum-graecum 939.764±0.01, L. sativum 551.63±0.02, A. sowa 306.34±0.06, L. cephalotes 233.19±0.03, T. cordifolia 211.76±0.02, E. alba 202.67±0.02, and C. reflexa Roxb. 145.09±0.09 mg milligram gallic acid equivalent per gram. The flavonoid content estimation showed T. cordifolia 852.07±0.11, L. sativum 553.81±0.05, E. alba 322.13±0.02, A. sowa 329.02±0.05, L. cephalotes 164.93±0.02, and C. reflexa Roxb. 146.37±0.00 mg milligram quercetin equivalent per gram. The antioxidant potential showed by E. alba IC50 33.48±0.82 μg/ml and the values ranged from E. alba 33.48±0.82 to A. sowa 47.62±1.09 μg/ml. The α-amylase inhibitory activity showed by A. sowa 76.78±2.00–E. alba 777.36±9.66 μg/ml. The result of brine shrimp toxicity showed LC50 value >1000 μg/ml. Among the seven plant extracts, only the plant extract of E. alba showed a zone of inhibition 14 mm against Staphylococcus aureus. Conclusions: The plant extract of T. foenum-graecum showed the highest phenolic content, and T. cordifolia showed the highest flavonoid content. The highest antioxidant potential exhibited by E. alba and the highest α-amylase inhibition activity showed by A. sowa. The plant extract of E. alba showed moderate antibacterial activity against S. aureus. All plant extracts were found non-toxic against brine shrimp larvae although further study is needed to assess its mechanism of action.